The Effect of Relaxation Guided Imagery and Foot Massage Techniques on Anxiety Level in Stroke Patients - Edelweis, Riena (WMJ (Warmadewa Medical Journal), 2019)
Stroke causes paralysis of one side of the body (hemiplegia). Powerlessness reduces the enthusiasm of life, causing emotional changes in the form of anxiety. Various interventions can be done to overcome this condition, including both pharmacological and non-pharmacological. Examples of the non-pharmacological interventions are the relaxation guided imagery and foot massage. This research design used an experimental study with non-equivalent control group design. The sample size of 60 respondents consisted of 3 groups and 1 control group with each group consisting of 15 respondents. This study used univariate data analysis with frequency distribution tables, bivariate analysis with paired t-test for paired groups and unpaired groups used independent t-test with significance level â‰¤ 0.05. The results showed that relaxation guided imagery or foot massage and the combination of both affected anxiety with p-value 0.01; there is a difference in the group before doing the treatment value Ï-value 0.812 Conclusion: stroke patients who are given an intervention for 30 minutes for 2 weeks along with standard treatment can reduce anxiety on a mild scale.